Design Principles for Neurorobotics - Krichmar, Jeffrey L.; Hwu, Tiffany J. (Frontiers in Neurorobotics, 2022)
In their book "How the Body Shapes the Way We Think: A New View of Intelligence", Pfeifer and Bongard put forth an embodied approach to cognition \citep{pfeifer2006}. Because of this position, many of their robot examples demonstrated ``intelligent'' behavior despite limited neural processing. It is our belief that neurorobots should attempt to follow many of these principles. In this article, we discuss a number of principles to consider when designing neurorobots and experiments using robots to test brain theories. These principles are strongly inspired by Pfeifer and Bongard, but build on their design principles by grounding them in neuroscience and by adding principles based on neuroscience research. Our design principles fall into three categories. First, organisms must react quickly and appropriately to events. Second, organisms must have the ability to learn and remember over their lifetimes. Third, organisms must weigh options that are crucial for survival. We believe that by following these design principles a robot's behavior will be more naturalistic and more successful.